Pharmacogenetics of 5-fluorouracil: anew way to trounce thegastric cancer - Nath, Nibendu; Kumar, Munish; Mazumder, Tarikul Huda (Asian Journal of Medical Research, 2014)
Gastric cancer cases are significantly increasing worldwide. In fast few years varietiesofchemotherapy drug are developed for the treatment of gastric cancer. Among these drugs 5-fluorouracil (5-FU) is broadlyin used.Effectiveness of 5-FU get significantly reduced due to single nucleotide polymorphisms (SNP) in drug metabolizing enzymes (DME). Thus due to the SNP, adverse drug reaction arereported in cancer patient. In order to minimize the side effect, personalized medicine has to be developed according to the individual’s genotype, wherepharmacogeneticscan add a boost in chemotherapyregime.The US Food and Drug Administration (FDA) had sanctioned eighty numbers of drugsholding genetic information.In this review, we discussimpact of polymorphisms in four specific drug metabolizing enzyme; Dihydropyrimidine dehydrogenase (DPD),Thymidylate synthase (TYMS),Methylenetetrahydrofolatereductase(MTHFR) andThymidylatephosphorylase(TP)and their effects on 5-fluorouracil.